Psychological and Pedagogical Peculiarities of Romanian Students’ Initial Socialization in Bukovina. - Sobkov, Yuriy; Sobkova, Svitlana (Revista Românească pentru Educaţie Multidimensională., 2020)
The article deals with the issue of students’ socialization during their studies at the university. The main peculiarity of the research under discussion is its focus on the contingent of students, who represent ethnic minorities in such a multiethnic area of Ukraine as Bukovina. The article lays particular emphasis on the peculiarities of such students’ socialization at the initial stage of their university studies through comparing the obtained results of learning social-psychological adaptation as a part of the socialization process, as well as through the factors affecting it. The results, obtained within Romanian and Ukrainian study groups, are compared. The authors of the article have carried out the data analysis for each category of respondents. In this respect, they have traced the difference in first-year students’ social-psychological adaptation. Based on the results of empirical research, the distribution of the levels of functioning of personal adaptability for each individual category of respondents was carried out, followed by comparative analysis. The empirical data obtained are described for Ukrainian and Romanian students in ethnically homogeneous and ethnically diverse academic groups. Within the study of the peculiarities of social-psychological adaptation as a component of the process of personal socialization, the study of the levels of personal and reactive anxiety was conducted. In addition, results were obtained concerning the study of the characteristics of social stress and general anxiety in the institution. Thus, on the basis of the analysis of diagnostic data, the description of the main psychological and pedagogical problems that influence the process of socialization of students representing the ethnic group “Romanians” (at the initial stage of their studies at the university) has been made.
Keywords: ethnic minority; social-psychological adaptation; socialization; personal anxiety; social stress; general educational anxiety.